Nandong as a culture-based effort to overcome food security toward COVID-19 pandemic situation in Simeulue Island. Issue 2 (July 2021) - Zulkarnain,; Lubis, T; Ramlan,; Dardanila,; Hasrul, S; Shaumiwaty,; Saputra, N
Abstract: This research discussed Oral Tradition Nandong (OTN) role through its performance of advice tradition in Simueluenese toward the agricultural sector. Further, it described how the performance supported food security during the lockdown period of the COVID-19 pandemic. The location of the research was on Simeulue Island. The data were collected by doing depth-interview and observation. The anthropolinguistic approach was used in this research. The research presented a model of food security in a rural area that deliberates both natural conditions and human effort. It showed that the role of OTN affected tenacity for surviving their food security as a concept. It was delivered through their daily activity and on some occasions. In those moments, the procedure in farming and cultivating are shared in a frame of advice. The obedience to obeying advice had affected Simeuluenese way of having access to sufficient food as their food security. This effort protected them from lack of food (especially the primary food) during lockdown situations caused by the COVID-19 pandemic. It can be concluded that OTN has an important role and should be accounted for in the agricultural sector for food security. Oral tradition as a medium to store and share knowledge and experiences built a cultural-based effort to maintain Simeuluenese agriculture for food security.